Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.3390/en13195045
|View full text |Cite
|
Sign up to set email alerts
|

Scalability of Low Carbon Energy Communities in Spain: An Empiric Approach from the Renewed Commons Paradigm

Abstract: Through the implementation of low carbon-based energy systems and participatory modes of governance, there are countless collective initiatives progressing towards a sustainable and resilient energy model. Local alternatives necessarily have to be able to scale in order to address global challenges. From the renewed paradigm of the commons, this empirical research provides a precise picture of the present scalability of these (self) transformative initiatives in Spain. Based on the identification and qualitati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 30 publications
(23 reference statements)
0
6
0
Order By: Relevance
“…In Spain, two main barriers have already been identified: the high costs of a distributed system [1], and the current energy auction system which might discriminate smaller citizens initiatives in favor of larger operators [13]. In the area of Social capital, barriers include issues of unequal participation [63] and engrained patterns of energy consumption behaviors which may be difficult to change [64]. Research has also identified gender issues with women voices being underrepresented within LEC initiatives [49].…”
Section: Literature Review: the Case Of Spainmentioning
confidence: 99%
See 3 more Smart Citations
“…In Spain, two main barriers have already been identified: the high costs of a distributed system [1], and the current energy auction system which might discriminate smaller citizens initiatives in favor of larger operators [13]. In the area of Social capital, barriers include issues of unequal participation [63] and engrained patterns of energy consumption behaviors which may be difficult to change [64]. Research has also identified gender issues with women voices being underrepresented within LEC initiatives [49].…”
Section: Literature Review: the Case Of Spainmentioning
confidence: 99%
“…From an environmental perspective (natural capital), there is general consensus on the high potential for significantly reduced greenhouse gas emissions in Spain and the EU [1,46,67]. Technological opportunities (physical capital) include a potential improvement in the efficiency of the energy system through local power generation as this will not need to be transported long distances [1], and a more resilient and adaptable energy system overall [26,63].…”
Section: Literature Review: the Case Of Spainmentioning
confidence: 99%
See 2 more Smart Citations
“…Academic literature has also shown interest in how community energy interacts with energy justice, redistribution of costs, and the benefits of the transition, particularly for lowincome households (see, for example, [15][16][17][18]). Similarly, the creation, scalability, and initial conditions for community energy initiatives have been researched in specific countries or theoretical approaches [19][20][21]. An overarching finding is that community energy is heterogeneous, both in its structures and objectives [22].…”
Section: Introductionmentioning
confidence: 99%